THE ADSORPTION OF WATER ON SRTIO3(100) - A STUDY BY ELECTRON-ENERGY LOSS AND PHOTOELECTRON SPECTROSCOPIES - Egdell, R; Naylor, P (1982)
The adsorption of H2O and D2O on SrTiO3(100) have been studied by high-resolution electron energy loss spectroscopy and He(II) photoemission. Water does not adsorb at room temperature on the defect-free surface, but binds strongly in oxygen vacancy sites generated by argon ion bombardment. The available experimental evidence favours non-dissociative adsorption. © 1982.